Impairment of mitochondrial dynamics: a target for the treatment of neurological disorders?. (May 2013) - Su, Yu-Chin; Qi, Xin
Mitochondrial dysfunction has long been appreciated in the pathogenesis of various neurological disorders. However, the molecular basis underlying the decline in mitochondrial function is not fully understood. Mitochondria are highly dynamic organelles that frequently undergo fusion and fission. In healthy cells, the delicate balance between fusion and fission is required for maintaining normal mitochondrial and cellular function. However, under pathological conditions, the balance is disrupted, resulting in excessive mitochondrial fragmentation and mitochondrial dysfunction. The impaired fusion and fission processes can lead to apoptosis, necrosis and autophagic cell death and seem to play causal roles in the progression of acute and chronic neuronal injuries. In this article, important aspects of what is currently known about the molecular machinery regulating mitochondrial fission and fusion in mammalian cells is summarized. Special emphasis will be given to the consequences of disregulated mitochondrial morphology in the pathogenesis of neurological diseases.